Simplified Modeling, Simulation and Performance Analysis Using Circuit Model for a Corporate Feed Microstrip Patch Array - Soh, Ping Jack (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org